بلوچی گیدی قصہانی ہمدپی: Similarities among Balochi folktale - Ali, Tanveer; Mehr, Dr.Rahim Bakhsh (Hanken, 2018)
In the ancient times people were lived together with the same civilization, culture, society and nature. Primarily, the stories were created and told by them and the stories came from one person to another one simultaneously. Nowadays, every nation has its own stories, but similar in subjects. The Orientalists and Baloch Scholars have collected many folk stories and written them into their own dialects and style. In the Balochi language, there are many folk stories with the similar themes, but the storytellers and writers have told and written them in different styles and techniques with their own words. This paper highlights the similarity and relationship of balochi folk stories